Management of Nonpregnant Women with Elevated Human Chorionic Gonadotropin - Bernd C. Schmid; Aimee Reilly; Martin K. Oehler (Case Reports in Obstetrics and Gynecology)
Human chorionic gonadotropin (hCG) is useful in evaluating and monitoring early pregnancy as well as trophoblastic disease. Here we describe the management of women with elevated serum human chorionic gonadotropin in a case of a 51-year-old female who was unsuccessfully treated for ectopic pregnancy. She was subsequently diagnosed with pituitary hCG production, which should be considered as differential diagnosis before treatment is initiated.